프로젝트 학습에서의 대학생 경험에 대한 관찰연구 - 박영주; 박진희 (교양교육연구, 2023)
학습자들의 지속 가능한 핵심역량의 개발에 대한 사회적 기대는 대학 교육의 혁신적인 교수학습법변화를 요구한다. 프로젝트 학습은 학습자가 예측불가능하고 복잡한 문제 상황에 직면하는 실제 상황에대비하여 의미있는 학습이 이루어지도록 주도적이고 협력적인 학습을 가능하게 한다. 본 연구는 이러한팀 프로젝트 수업에 주목하여 대학에서 진행되는 팀 프로젝트 수업의 학습 과정에서 행해지는 실제학습자들의 맥락적 행동 양상에 대해 분석하고 그 특성을 살펴보았다. 팀 활동 장면이 녹화된 비디오자료를 기반으로 학습자들의 상호작용 과정 중 특히 대화 상황을 분석하였다. 그 결과는 다음과 같다. 첫째, 프로젝트 활동의 목적을 규정하기 위한 학생들의 논의 과정은 배운 지식의 적용 또는 활용이라기보다 학습자들의 상호작용을 통해 자신들의 경험의 범위를 넘어서는 안목의 확장으로서 배움의 과정임을확인할 수 있었다. 둘째, 프로젝트 결과물의 주제와 방향에 대해 논의하는 학생들의 협력 과정은 협력적상호작용이 의견일치나 동의, 적극적 소통에 기반할 것이라는 일반적 기대와 달리 개별적 차이에 기반한동의와 암묵적 인정의 방식으로 이루어지고 있었다. 셋째, 학생들은 실제 경험을 통해 예측의 기반이되었던 통상적 경험의 범위 안에 갇힌 동일성의 논리를 넘어 상식과 통념으로 인해 놓치고 있던 의미에눈을 돌려야 함을 성찰하고 이를 통해 문제를 새롭게 규정하는 데로 나아가고 있었다. 넷째, 실제프로젝트 활동의 과정에서 실행된 교수자의 피드백은 일반적 지식과 달리 실제 상황에서 발생한 문제해결을 지원함으로써 학생들의 문제 해결 과정에서 도구이자 지렛대로 기능할 수 있음을 확인할 수있었다. 본 연구의 결과가 팀 프로젝트 학습 과정에서 실제 학습자에게 어떠한 경험을 가능하게 하는지에대한 기초 연구 자료로서 팀 프로젝트 학습의 활성화에 기여할 수 있기를 기대한다. Social expectations for the development of sustainable core competencies of learners require innovative changes in teaching and learning methods in university education. Project learning enables proactive and cooperative learning so that meaningful learning can take place in preparation for real situations in which learners face unpredictable situations and those involving complex problems. This study focuses on these team project classes, analyzes the contextual behavioral aspects of actual learners during the learning process of team project classes conducted in universities, and examines their characteristics. As a result, the study confirmed that the process of discussion among students to define the purpose of the project activity is a learning process in itself. It is also serves as an extension of their perspective that goes beyond the scope of their experience through their interactions, rather than the application or utilization of learned knowledge. In addition, unlike the general expectation that cooperative interaction will be based on consensus, agreement, and active communication, the cooperative process of students discussing the subject and direction of the project outcome is conducted through tacit recognition of individual differences and agreement on these differences. Moreover, through actual experience, students reflected on the need to focus on the meaning that was missing due to common sense and conventional wisdom, and which goes beyond the logic of identity confined within the range of ordinary experience that was the basis of prediction. Through this, they were able to make progress in redefining the problem. Finally, the study confirmed that the instructor's feedback, which was implemented during the actual project activity process, can function as a tool and and as leverage in the process of the students' problem-solving abilities by supporting the problem-solving that occurred in real situations, unlike in general knowledge. It is expected that the results of this study will contribute to the vitalization of team project learning as basic research material to determine what kind of experiences are possible for actual learners in the team project learning process. KCI Citation Count: 1